Biologic Immunomodulatory Drugs and Infection in the Respiratory Tract of Nonhuman Primates. (February 2021) - Flandre, Thierry D.; Piaia, Alessandro; Cary, Maurice G.
Though rare due to measures and practices to control the risk, infections can occur in research and toxicology studies, especially in nonhuman primates (NHPs) exposed to xenobiotics, particularly immunomodulatory drugs. With such xenobiotics, immunocompromised or immunosuppressed animals will not be able to mount a protective response to infection by an opportunistic pathogen (bacteria, virus, parasite, or fungus) that might otherwise be nonpathogenic and remain clinically asymptomatic in immunocompetent animals. The respiratory tract is one of the most commonly affected systems in clinic, but also in toxicology studies. Pulmonary inflammation will be the main finding associated with opportunistic infections and may cause overt clinical disease with even early sacrifice or death, and may compromise or complicate the pathology evaluation. It is important to properly differentiate the various features of infection, to be aware of the range of possible opportunistic pathogens and how they may impact the interpretation of pathology findings. This review will present the most common bacterial, viral, parasitic, and fungal infections observed in the respiratory tract in NHPs during research and/or toxicology studies.